2010
DOI: 10.1103/physrevlett.104.253002
|View full text |Cite
|
Sign up to set email alerts
|

Ultraintense X-Ray Induced Ionization, Dissociation, and Frustrated Absorption in Molecular Nitrogen

Abstract: Sequential multiple photoionization of the prototypical molecule N 2 is studied with femtosecond time resolution using the Linac Coherent Light Source (LCLS). A detailed picture of intense x-ray induced ionization and dissociation dynamics is revealed, including a molecular mechanism of frustrated absorption that suppresses the formation of high charge states at short pulse durations. The inverse scaling of the average target charge state with x-ray peak brightness has possible implications for singlepulse ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
209
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(223 citation statements)
references
References 15 publications
11
209
3
Order By: Relevance
“…Generally, X-ray photoabsorption is suppressed in high-fluence experiments when the time between successive photoabsorption events is shorter than the Auger lifetimes. This effect has been referred to as frustrated absorption and was observed for atoms 29 and small molecules 34 ; our results show a similar trend for C 60 . The effect is observable in our modelled data for single-carbon atoms in long (90 fs) and short (4 fs) pulses (Fig 4a-c).…”
Section: Femtosecond Ionization Dynamics the Linac Coherent Lightsupporting
confidence: 75%
See 3 more Smart Citations
“…Generally, X-ray photoabsorption is suppressed in high-fluence experiments when the time between successive photoabsorption events is shorter than the Auger lifetimes. This effect has been referred to as frustrated absorption and was observed for atoms 29 and small molecules 34 ; our results show a similar trend for C 60 . The effect is observable in our modelled data for single-carbon atoms in long (90 fs) and short (4 fs) pulses (Fig 4a-c).…”
Section: Femtosecond Ionization Dynamics the Linac Coherent Lightsupporting
confidence: 75%
“…For a direct comparison of experiment and theory, the XFEL pulse properties must be known. Calibrations revealed that the XFEL parameters can differ from the nominal values provided by LCLS, for example, the actual pulse duration is 50-60% of the nominal value as also indicated by earlier studies 29,34 . Our calibrations indicated that for the nominal pulse durations of 7, 60 and 150 fs full-width at half-maximum recorded with the experimental data, actual pulse durations of 4, 30 and 90 fs, respectively, are more appropriate.…”
Section: Femtosecond Ionization Dynamics the Linac Coherent Lightmentioning
confidence: 96%
See 2 more Smart Citations
“…Unprecedented focused intensities at ultrashort wavelengths have led to the discovery of xray phemonena such as nonlinear multiphoton absorption in atoms, molecules, and clusters [6][7][8][9][10], atomic x-ray lasing [11,12], induced transparency or saturable absorption [6,9,10,[13][14][15], stimulated emission [16][17][18], and second harmonic generation [19]. Understanding these fundamental processes underpins the use of ultraintense XFEL pulses and fuels the dream of 3D imaging of single biomolecules using the "diffract-before-destroy" method initially envisioned at the dawn of the XFEL-enabled era of x-ray science [20,21].…”
Section: Introductionmentioning
confidence: 99%